A biomechanically optimized knitted stent using a bio-inspired design approach. Issue 4 (March 2016) - Singh, Charanpreet; Wang, Xungai
Vascular implants have always been a key area of research in medical textiles. Knitted structures have been proven to be suitable for stent applications on the basis of their looped mesh geometry, structural flexibility and ease of manufacturing. However, there are biomechanical constraints of plain knit constructions that can result in clinical complications after implantation and hence cannot be ignored. This study reports a new segmented knit design inspired by structural metamerism observed in the body design of some invertebrate animals. Metamerism is the phenomenon of having a linear series of body segments fundamentally similar in structure, but assigned to perform different functions. It was hypothesized that utilization of this simple and yet effective biological design approach in stent construction could improve the degree of control for optimizing stent biomechanical properties. The proposed segmented stent was constructed by incorporating an elastic filament component into a polyethylene terephthalate knitted stent at specific intervals along its length, also known as the 'Plating Technique'. This technique generates a structure with alternately arranged stiff and elastic knitted sections which equip the stent with vital structural support and volumetric compliance properties, respectively. The stent design parameters (filament diameter, loop length, segmentation plan) were optimized to achieve significantly better biomechanical performance (bending flexibility, compression resistance, volumetric expansion, longitudinal extensibility) than a plain knit stent.